The use of digital touch screen technology to deliver reminiscence therapy among people with dementia in Jordanian care homes: a mixed‐method feasibility study. Issue 2 (5th January 2022) - Abdalrahim, Asem; Carter, Tim; Abu Khait, Abdallah; Clissett, Philip; Blake, Holly
Abstract: Background: Using technology to deliver psychosocial interventions such as reminiscence therapy (RT) to people with dementia may improve their mental health. Yet, establishing the feasibility of digital interventions in low‐ to middle‐income countries is still in the early stages. This study aimed to: (i) determine the feasibility of using digital touch screen technology to deliver RT among people with dementia living in Jordanian care homes; and (ii) compare study outcomes pre‐ and post‐reminiscence sessions to investigate whether specific outcomes are sensitive to change and explore the acceptability and experiences of the intervention. Methods: A pragmatic mixed‐method study design was implemented. Sixty residents with dementia were recruited from two Jordanian care homes (Site 1: n = 35; Site 2: n = 10). A process evaluation was conducted alongside a single‐group pre‐post‐intervention study. The intervention involved 10 supported RT sessions of up to 1 h each, delivered over 5 weeks. Feasibility was determined by assessing the rate of recruitment, adherence, retention, data completion, implementation fidelity, and adverse events. Qualitative semi‐structured interview questions were used to explore experience and acceptability, and data were thematically analysed. Results: Response rate was 100%; loss to follow up at post‐intervention was 25%. Median session attendance for those who received the intervention was 80%. No serious adverse events were reported. A positive, statistically significant and clinically relevant difference was found in all outcome measures before and after reminiscence sessions. Qualitative findings suggest that digital RT intervention is generally well accepted by people with dementia who reported positive changes, including enhanced communication and cognitive abilities. Conclusion: Using digital touch screen technology to deliver RT is feasible and acceptable among people with dementia in Jordanian care homes. Digital RT intervention is a promising approach to improving mental health and communication for people living with dementia.